The Role in SLA played by Universal Grammar - Maria Elizabet Ritonga (Journal of Applied Linguistics, 2022)
One important issue in current language acquisition research is whether the acquisition of a second language is fundamentally different from that of the first language. Researchers approaching second language acquisition (SLA) from the linguistic perspective often relate this issue to the availability of Universal Grammar to second language acquisition. The main focus of this paper is to examine the role of Universal Grammar in the second language acquisition and to what extent it plays in the process. To illustrate this, the four access hypotheses or theories were given. Keywords: Universal Grammar, Second Language Acquisition